Four Pins Assisted Reduction of Complex Segmental Femoral Fractures： a Technique for Closed Reduction - 郑占乐 于贤 许国强 陈伟 张英泽 焦振清 (Journal of Huazhong University of Science and Technology. Medical sciences, 2014)
Complex segmental femoral fractures are usually not amenable to closed reduction. The purpose of this study was to evaluate a series of patients who had undergone four pins assisted reduc- tion and intramedullary nail fixation to determine the therapeutic effect of this closed reduction tech- nique. Between December 2010 and January 2013, 15 consecutive patients with segmental femoral fractures were treated with four pins assisted reduction at our hospital. The patient was placed in a supine position on a radiolucent fracture table and a. gentle traction was attempted on the limb. Usu- ally, the proximal fracture segment exhibited the typical deformity of flexion, external rotation, and abduction, the middle segment exhibited adduction and distal fracture segment exhibited flexion. Four Schanz pins were placed percutaneously to fix one cortex and did not penetrate into the me- dullary cavity, and the ＂T＂ sharp handles were fixed on the Schanz pins. The fragments were then re- duced by reversing the deforming forces for segmental fractures by two assistants~ And then, the re- duction could be easily achieved and intramedullary nail fixation was performed. Radiographs were evaluated for the quality of the reduction and fracture union. Closed reduction was achieved in all pa- tients using the four pins technology. All 15 fractures united uneventfully. No patient had a rotational malunion or limb length discrepancy at the time of the last follow-up. Thirteen of the fifteen （86.7%） patients had anatomic reduction and two of them （13.3%） had minor varus alignment of 3° and 5°. Knee stiffness was Observed in 2 patients and no implant failure was observed. Surgical treatment of complex segmental femoral fractures With four pins assisted reduction and intramedullary nail fixation techniques can result in excellent reductions and a high union rate.